Pedestrians' perceptions of route environments in relation to deterring or facilitating walking - Andersson, Dan; Wahlgren, Lina; Schantz, Peter (Frontiers in Public Health, 2023)
Background Every walk takes place in a route environment, and it can play an important role in deterring or facilitating walking, and it will always affect the environmental unwell – wellbeing of pedestrians. The aim of this study is to illuminate which the important route environmental variables are in this respect. The focus is therefore on pedestrians´ perceptions of route environmental variables and how they relate to overall appraisals of route environments as hindering – stimulating for walking and unsafe – safe for reasons of traffic. Methods Commuting pedestrians in the inner urban area of Stockholm, Sweden (n = 294, 49.5 ± 10.4 years, 77% women), were recruited via advertisements. They evaluated their own commuting route environments using a self-report tool, the Active Commuting Route Environment Scale (ACRES). Correlation, multiple regression, and mediation analyses were used to study the relationships between the variables and the outcome variables. Results Aesthetics and greenery combined appear to strongly stimulate walking, whereas noise, a proxy for motorized traffic, hinders it. Furthermore, aesthetics is positively related to traffic safety, whereas conflicts have the opposite role. Conflicts is as an intermediate outcome, representing several basic environmental variables, whereof some were directly and negatively related to unsafe – safe traffic. Conclusion Route environmental variables appear to be potent factors in deterring or facilitating walking. This knowledge is of importance for policymakers and urban planners when designing route environments with the aim of attracting new pedestrians, and simultaneously stimulating those who already walk to keep on.